No silêncio dos arquivos : relatos de viajantes que percorreram Mato Grosso – (1808-1864) - Martins, Dulcinéia Silva (2014)
This dissertation brings notes and observations on the reports of travelers who visited Mato Grosso in the period 1808-1864, and were silenced in the documents of the Public Archives of the State of Mato Grosso. According to the survey covering, travel documents is becoming a traveler lives reborn from the lines drawn by ancient narrators memoir reconstructing life histories. In each line covered, a dream, a wish, a story and new facts and relevant to someone or something that unfolds in exciting readings in painstaking and thorough research events. The impressions left by these travelers about the places visited are always present in many ways. Clergymen, militaries, engineers, among others, were the offices of these men. Even being only men, silenced travelers, women also attended and completed the routine of Mato Grosso society. Between trips it was observed to be impossible the silence about such replete sources of political and social quarrels, passions, stories about diseases and natural wealth. Brother Angelo of Caramanico, Engineer Pedro Dias Paes Leme, Ensign Antonio João Ribeiro and Frei Mariano Bagnaia, although known regional history, were not addressed as travelers. Are also given the following rating: Lieutenant Francisco Bueno da Silva, Lieutenant Manoel Simoes Henriques, Sergeant John Manuel Henrique, Captain Antonio Joaquim Xavier del Valle, José Ribeiro do Nascimento, Hypólito Simas Bittencourt , Luiz Soares Viégas, Joaquim do Espírito Santo Barbosa, Major Jozé Constantino de Oliveira, Antonio Rodrigues Itunamas, Manoel Carneiro de Campos, Juan Mendes Salgado. Also a special emphasis was given to the situation of medicine that was being practiced at the time as: therapeutic employed, the processes of healing, types of medications, previous treatments, quarantine instructions, instruments and medicines used by apothecaries, pathological statistical maps, maps sick of hospitals and employed diets, taken from information provided by travelers and some doctors as Dr. Antonio Luis Patrício da Silva Manso (1830); Dr. Macário Pamphilo Nogueira (1855); Dr. Mendonça Rivani (1856); the 2nd surgeon José Cândido da Silva Murici (1859) ; the Deputy Surgeon - Major of the Army, Dr. José Antonio Murtinho (1856); the "Pharmacêutico " Doctor John Adolpho Josetti among others. The stated and "unsaid" in this Master's thesis was the conductor for the proposed restoration of Mato Grosso’s memory by travelers.